2016
DOI: 10.1097/md.0000000000005629
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in the intensive care unit professionals

Abstract: Background:Burnout has been described as a prolonged response to chronic emotional and interpersonal stress on the job that is often the result of a period of expending excessive effort at work while having too little recovery time. Healthcare workers who work in a stressful medical environment, especially in an intensive care unit (ICU), may be particularly susceptible to burnout. In healthcare workers, burnout may affect their well-being and the quality of professional care they provide and can, therefore, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
216
6
26

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(293 citation statements)
references
References 53 publications
16
216
6
26
Order By: Relevance
“…16 However, other various studies found age, gender, level of education, marital status to be associated with burnout. 3,17,18 Conversely, in this study high level of burnout was found among married participants but there was no significant association between marital status and burnout (P >0.05). In addition, it was found that having a partner to share with, helps to overcome psychological issues which explains low level of burnout among married individuals.…”
Section: Sociodemographic Characteristicscontrasting
confidence: 64%
See 4 more Smart Citations
“…16 However, other various studies found age, gender, level of education, marital status to be associated with burnout. 3,17,18 Conversely, in this study high level of burnout was found among married participants but there was no significant association between marital status and burnout (P >0.05). In addition, it was found that having a partner to share with, helps to overcome psychological issues which explains low level of burnout among married individuals.…”
Section: Sociodemographic Characteristicscontrasting
confidence: 64%
“…20 Similar to this, a systematic review revealed that master's in nursing is a risk factor of burnout P=0.003. 3 However the majority of the participants [51(85%)] in the current study held diploma in nursing qualification which may explain the lack of association between the level of education and level of burnout.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 72%
See 3 more Smart Citations